Methods of diagnostics and treatment of cystitis in cats - Дмитренко, Н. І. (Scientific Progress & Innovations, 2017)
The conducted researches have revealed that various pathological changes in the organ: change in size, thickness and integrity of the wall, heterogeneity of urine may be detected by ultrasound. Diffuse or total thickening of the bladder wall was observed in sick animals with cystitis. It was visualized in the form of a sharp epocial contour, features of detachment and separate unevenly thickened echo-negative sites and edema of the mucous membrane. Changes in the properties of urine for cystitis in cats were characterized by a decrease in relative density and an increase in pH. The number of epithelial cells of the bladder and urinary tract and white blood cells increased in urine sedimentation.